Avaliação tomográfica da reabsorção radicular de molares após mesialização utilizando mini-implantes como ancoragem - Vasconcelos, Karla de Souza (2018)
Introduction: The purpose of this retrospective study was to evaluate and quantify the apical root resorption (RRA) in the mesialized molars in the atrophic alveolar ridge area. Methods: The sample consisted of 11 patients, of both sexes (5 females and 6 males), in a total of 16 mesialized teeth of both arches (7 in the maxilla and 9 in the mandible). The age of treated patients ranged from 19 years to 55 years at the beginning of treatment (initial mean age: 36 years and 5 months), with an average treatment time of 23 months. The mesialization was performed anchored in mini-implants with Niti springs, using a mean force of 300 grams. The sample was evaluated by means of cone-bean computed tomography (CBCT), in two periods, at the beginning of treatment (T1) and after 4mm of mesialization (T2). Root resorption was measured by the difference in root lengths (T2-T1). To assess the measurement, we used as reference the distance from the floor of the pulp chamber to the root apex. Root length was measured in a specific software (OnDemand3Ddental) and analyzed by means of the paired t test and Pearson’s Correlation Coefficient, adopting a significance level of 5% (p <0.05). Results: There was a statistically significant resorption only in the mesial and distal roots of the mesialized molars, with a mean reduction of 0,69 mm in the mesial root (-6.2%) and 0,83 mm in the distal root (-7.4%). Conclusion: The closure of space through tooth movement in an atrophic alveolar ridge was identified as a risk factor for ARR. However, the amount of apical root resorption was considered clinically irrelevant.